Coitus Interuptus sebagai Upaya Pencegah Kehamilan Dalam Hukum Islam (Studi Komparatif Menurut Al Gazali dan Ibnu Al-Qayyim) - Tomi Agustian; Lentiara Putri (El-Ghiroh : Jurnal Studi Keislaman, 2020)
This study aims to describe and analyze the opinions of al Gazâlî and Ibn Qayyim al-Jauziyyah regarding the right to enjoy sexual relations for husbands and wives during interrupt intercourse, a literature study research method. conclusions al-Gazalî is a memorandum of understanding of the Shyay'iyyah scholars, allowing the alliance to interrupt absolutely, almost the same as al-Gazalî, Ibn al -Qayyim also allows the practice of interrupt intercourse but with the condition of permission from the wife first. Mafhum mukhalafah if the wife does not allow it, then interrupt intercourse should not be done. The evidence used by Ibn al-Qayyim for the ability of intercession is the same as that of al-Gazâlî, the hadith from Jâbir regarding the ability of this practice as an attempt to prevent pregnancy at that time. Ibn al-Qayyim's view is more concerned with women's rights than that of al-Gazalî because the wife's permission is used as a condition for the ability to have intercourse with interruptions.